Dynamic instability of a double curved shallow sandwich electromagnetic shell with a three-phase nanocomposite core - Cong, Pham Hong; Huong, Nguyen Van; Duc, Nguyen Dinh; Chien, Trinh Minh (Vietnam Journal of Mechanics, 2026)
This study examines the dynamic instability region (DIR) of a double-curved shallow sandwich electromagnetic (DSEM) shell containing a three-phase nanocomposite core and supported by an elastic foundation. The governing equations for nonlinear dynamic stability are formulated using first-order shear deformation theory (FSDT) combined with von Kármán geometric nonlinearity. The Galerkin method is applied to derive the nonlinear ordinary differential equations, and Bolotin’s method is used to identify the DIR of the shell structure. Parametric analyses are conducted to evaluate the influences of electromagnetic fields, shell geometry, and core material properties on the nonlinear DIR.